Adaptability of GPS/BDS broadcast ionospheric models to solar activities. Issue 9 (1st May 2019) - Song, Shuli; Cheng, Na; Xie, Hui; Zhou, Weili
Abstract: Solar activity induces ionospheric disturbances, which can reduce the performance of the Global Navigation Satellite System (GNSS). Broadcast ionospheric models (BIMs), used to correct ionospheric delay for single-frequency users, the features and performance of which under ionospheric disturbance conditions are still not understood clearly. In this study, we analyzed the adaptability of the Global Positioning System/BeiDou Navigation Satellite System (GPS/BDS) BIMs and ionospheric total electron content (TEC) anomalies over China during 12 X-class and M-class large solar flare events during the solar active period in terms of the TEC, rate of TEC (ROT), and relative accuracy. Our study showed that during the solar flare occurrence the GPS-derived TEC over China may increase up to 5.0 TECUs within minutes, whereas the ROT may exceed 0.5 TECU/min. Relative to the GPS-derived TEC and ROT, both BDS and GPS BIMs cannot response so actively to these solar flares. However, in terms of relative accuracy, the BDS BIM performed with weaker influence from solar flares due to its updating of coefficients with high frequency, though the absolute accuracy of the BDS BIM has to be improved further.